necIntroduction to Social Work For the Human Development of Migrants - Carreón Guillén, Javier; Limón Domínguez, Gerardo Arturo (Trabajo Social UNAM, 2016)
The human development of migrants, understood as the establishment of freedom, opportunities, abilities and responsibilities, is interwoven in economic, political systems. It is a process based on the theories of Ludwig Von Bertalanffy, Niklas Luhmann and Armartya K. Sen, which entails the emergence of migratory flows as a function of economic flows. In this way, direct foreign investment in developed countries is confined to the organic composition of capital that, from the systemic perspective of development, involves migratory flows which make possible by the negentropy of emerging countries. Within this scenario, Javier Carreón Guillén and Gerardo Arturo Limón discuss the implication of migratory flows derived from the flows of investment in the maquiladora sector of Ciudad Juárez, Chihuahua, in northeast Mexico.